Design History Reader : An emerging vision for a new narrative - Coogan, Kristen (Eindhoven : Onomatopee Projects, 2025)
Written contributions by: Amina Hachimura, Alexina Federhen, Anna Doctor, Annabella Pugliese, Belle Bennet, Charles Li, Dar Saravia, Ellen Johnson, Flora Kerner, Grace Chong, Haya AlMajali, Julia Cheung, Kristina Shumilina, Lauren Had, Leila Garner, Maidha Salman, Natalie Seitz, Niharika Yellamraju, Olujimi Taiwo, Rayne Schulman, Rhea Jauhar, Rashina Wang, Risa Yamazaki, Shaimaa Sabbagh, Sheryl Peng, Sophie Zimbler, Tzu-Hsuan Huang, Winnie Mei, Xiuqi Ran and Yue Luo.
How can we — as people, as designers, as educators — contribute to change? How can we foster more enhanced cultures of empathy and inclusion? Design History Reader grapples with the paradox that while historians intentionally craft historical discourse based on collective knowledge, it often remains bound to a singular perspective. This book encourages a pluralistic approach to the teaching and narrating of the history of graphic design, presenting a history that actually reflects the diversity in the classroom and in the profession at large. Throughout this book, the Western design history canon is challenged through written research, highlighting under-known designers and design movements who deserve representation. In collaboration with Kristen Coogan, the students of History of Graphic Design from Boston University embraced a plural design history pedagogy, multiplying perspectives and bringing their own authentic experiences and lived histories into conversation — resulting in a range of stories representing both dominant and minority cultures. The concepts that tie these stories together become a contemporary vision of graphic design history and offer a new way to study, interact with, and perceive the narrative. Design History Reader is a dynamic starting point, open to interpretation and interrogation. It’s not anywhere near being fully representative but, instead, a living archive that will continue to expand as our collective research advances. [provided by publisher]
boek